Effectiveness Of Rosella Tea On Decreasing Blood Pressure In Hypertension Patients In Tulungagung District - Farida Farida; Yusuf Abdillah; Poppy Farasari (Universitas STRADA Indonesia, 2020)
The research design used pre experimental. The sampling technique uses quota sampling with a sample of 30 respondents. Design research was one group pretest-posttest. The study used a dose of 2 x 3 grams of dried rosella each day for seven (7) days. Test Statistics using Paired T test.The results of the study were obtained before the treatment as many as 26 respondents (86.7%) with the classification of stage 1 hypertension and after treatment to 18 respondents (60%), this was due to filling vacancies in the incidence of prehypertension and normal tension.normality test Kolmogorov-smirnof data is normally distributed. The results of thestatistical Paired T-testtest showed that the value of p systole = 0,000 and dyastole = 0.001 with α = 0.05 where p <α so that Ho was rejected, which means there was a decrease in the average blood pressure after giving rosella tea